2006
DOI: 10.1152/jn.01220.2005
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes in Electrophysiological Properties and Synaptic Transmission in Rat Intracardiac Ganglion Neurons

Abstract: Rimmer, Katrina and Alexander A. Harper. Developmental changes in electrophysiological properties and synaptic transmission in rat intracardiac ganglion neurons. J Neurophysiol 95: 3543-3552, 2006. First published April 12, 2006 doi:10.1152/jn.01220.2005. We charted postnatal changes in the intrinsic electrophysiological properties and synaptic responses of rat intrinsic cardiac ganglion (ICG) neurons. We developed a whole-mount ganglion preparation of the excised right atrial ganglion plexus. Using intracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
40
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 33 publications
8
40
0
Order By: Relevance
“…For electrophysiology, neurons were readily distinguished by their large somas (ϳ20 m diameter) with distinct nuclei, and projections from the cell bodies often apposed nearby cells (Fig. The membrane potential of Ϫ43 mV was determined by the zero-current voltage (V-track), and it compared favorably with that reported for rat intracardiac ganglion neurons by sharp glass microelectrodes (25). Values for passive electrical properties taken from whole cell patch-clamp recordings of cells 1 day in culture are shown in Table 2.…”
Section: Intrinsic Cardiac Neurons From Adult Mice Develop Neurites Imentioning
confidence: 90%
See 1 more Smart Citation
“…For electrophysiology, neurons were readily distinguished by their large somas (ϳ20 m diameter) with distinct nuclei, and projections from the cell bodies often apposed nearby cells (Fig. The membrane potential of Ϫ43 mV was determined by the zero-current voltage (V-track), and it compared favorably with that reported for rat intracardiac ganglion neurons by sharp glass microelectrodes (25). Values for passive electrical properties taken from whole cell patch-clamp recordings of cells 1 day in culture are shown in Table 2.…”
Section: Intrinsic Cardiac Neurons From Adult Mice Develop Neurites Imentioning
confidence: 90%
“…This work has provided evidence that, in addition to cholinergic efferent neurons, the intrinsic cardiac ganglia contain noradrenergic efferent neurons, local circuit neurons, and sensory neurons (3,7). Intrinsic cardiac neurons have been classified as phasic, accommodating/adapting, or tonic depending, respectively, on whether they discharge only one or two action potentials during a constant depolarizing current injection, several action potentials at a decreasing rate, or repetitive action potentials at a constant rate (1,25). Intrinsic cardiac neurons have been classified as phasic, accommodating/adapting, or tonic depending, respectively, on whether they discharge only one or two action potentials during a constant depolarizing current injection, several action potentials at a decreasing rate, or repetitive action potentials at a constant rate (1,25).…”
mentioning
confidence: 99%
“…The right atrial ganglion plexus and underlying myocardium were isolated from the dorsal surface of the atria. The preparation was pinned to the Sylgard (Dow-Corning, Midland, MI) covered base of a 35 mm tissue culture dish and superfused with a bicarbonate-buffered Krebs solution comprising (in mM): NaCl 118.4, NaHCO 3 25.0, NaH 2 PO 4 1.13, CaCl 2 1.8, KCl 4.7, MgCl 2 1.3 and glucose 11.1, gassed with Carbogen (95% O 2 :5% CO 2 ) to pH 7.4 (Rimmer and Harper, 2006). The recording chamber was continuously superfused (∼ 2 ml/min) with Krebs solution at 35 °C.…”
Section: Methodsmentioning
confidence: 99%
“…These studies revealed that cKOs exhibit sinus bradycardia (two-way ANOVA, P = 0.0012; Fig. 3 A and B) beginning at P12, corresponding to the developmental timing of sympathetic control of heart rate (28,29). At P6, before the sympathetic nervous system is thought to be functionally relevant for establishing basal heart rate, there is no difference between mutants and littermate controls ( Fig.…”
Section: Postnatally Shp2 Ckos Exhibit Diminished Neurite Outgrowth mentioning
confidence: 91%
“…Sympathetic (i.e., TH-positive) innervation is first observed at the base of the fetal heart; this innervation then extends onto the surface of the atria and eventually to the ventricles before following blood vessels into the ventricular wall to innervate the myocardium and project to the sinoatrial and atrioventricular nodes postnatally (27). The sympathetic innervation of the heart is not functionally relevant (i.e., does not control heart rate) until the second postnatal week of life in rodents (23,28,29), and the adult pattern of innervation is not fully achieved until 3 wk after birth (23,30). This developmental process requires nerve growth factor (NGF), which is produced by the target organ (the myocardium in the case of the heart) and is the main neurotrophic factor in establishing and maintaining sympathetic innervation (31).…”
mentioning
confidence: 99%